IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF SISWA KELAS III B SDN 115 PEKANBARU (PENELITIAN EKSPERIMEN QUASI) - Hendri Marhadi; Erlisnawati Erlisnawati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2015)
This research intend to know by its low grade in social studying student of class IIIB. Learning process is still dominated by teacher, while class discussion the student have been group not up on difference or student variety. Group discussion just have been done by seat. This research intend to know is it available see differences of the grade to social study student class III SD Negeri 115 Pekanbaru with learnings cooperative learning. cooperative's learning is activity series study that have been done by student in group to reaches to the effect learning already be formulated. This research is observational semi eksperiment (quation eksperiment).The subjek of this research is the student of class IIIB in SD Negeri 115 Pekanbaru that is from 2 classes, the total of class IIIB is 38 person and the total of class IIIC 37 person. the data analyzed tech that is used is t-test. the observational is have been done with three cycle, two times appointment work through material and once appointment pretest. Base of observational result have gotten pretest's studying result is found that among experiment class and control class average grade studying have no significan difference. Braze of experiment with control class to have t computing -2. 49dan t table 2,000. Based of the result to posttest's average value, known that student with cooperatives learning which is experiment class has average pretest 54,07 and posttest as big as 68,28 . Meanwhile control class has average pretest 62,70 and posttest as big as 64,05. Base of studying result rolled out point posttest experiment class and control class exist distinctive average, it can be concluded that exists distinctive result study among learned student by applying learning cooperative and learned student ordinary (conventional). So learning cooperative in social subject learning give impact to grade of study the better instead of social subject learning by use of conventional learning. This difference is based by afters marks sense difference among brazes experiment class and control class by use of t-quiz. The count of t acquired tcomputing 3.680 > ttable 2,000, Its mean the difference is exist which signifikan in class IIIB social study of class eksperiment student as by brazes control.Keywords: cooperative learning, students learned result